New Mixed Ligand Complexes; Synthesis, Spectral Analysis and Biological Activity - Enaam Ismail Yousif (Journal of Global Pharma Technology, 2019)
The formation, structural characterization of mixed ligand complexes of Co II, Zn II, Cd II and Hg II metal ions with the Schiff base ligand (Z)-3,4,5-trihydroxy-N'-(4-hydroxybenzylidene) benzohydrazide and 8-hydroxyquinolineare reported. Ligand and complexes were characterized by analytical and spectroscopic analyses including; FTIR, electronic and 1H, 13C-NMR spectroscopy, microanalysis, chloride content, thermal analysis, magnetic susceptibility and conductance. Physico-chemical techniques indicated the formation of complexes with four-coordinated arrangement in the solid and solution state. Biological activity of the prepared ligand and their mixed complexes were screened for their antimicrobial activity against four bacterial species (Staphylococcus aureus and Bacillus subtitles (G+)), Enterobacter and Escherichia coli (G-)). Biological data showed that complexes become potentially more active against these tested bacteria compared with the free ligandsKeywords: Mixed ligand complexes, Structural characterization, Spectral analysis, Biological activity.